2003
DOI: 10.1042/bj20030089
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a highly active pool of type II phosphatidylinositol 4-kinase in a p97/valosin-containing-protein-rich fraction of the endoplasmic reticulum

Abstract: Different phosphoinositides are synthesized in cell membranes in order to perform a variety of functions. One of the most abundant of these lipids is phosphatidylinositol (PI) 4-phosphate (PI4P), which is formed in human eukaryotes by type II and type III phosphatidylinositol 4-kinase (PI4K II and III) activities. PI4K II activity occurs in many different subcellular membranes, although no detailed analysis of the distribution of this activity has been reported. Using density gradient ultracentrifugation, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 40 publications
1
80
0
Order By: Relevance
“…1F). Western blotting of GFP-PtdIns4KII␣ HT1080 cell lysates with PtdIns4KII␣-specific antibodies (Waugh et al, 2003a) indicated that levels of ectopic expression were similar to those of endogenous protein and furthermore, when control and stably transfected cells were fractionated on sucrose density gradients both showed an identical distribution of endogenous protein, GFP-PtdIns4KII␣ protein and activity (data not shown). In addition, our GFP-PtdIns4KII␣ HT1080 cell line did not exhibit any disruption of the Golgi complex or mislocalisation of Golgi markers (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1F). Western blotting of GFP-PtdIns4KII␣ HT1080 cell lysates with PtdIns4KII␣-specific antibodies (Waugh et al, 2003a) indicated that levels of ectopic expression were similar to those of endogenous protein and furthermore, when control and stably transfected cells were fractionated on sucrose density gradients both showed an identical distribution of endogenous protein, GFP-PtdIns4KII␣ protein and activity (data not shown). In addition, our GFP-PtdIns4KII␣ HT1080 cell line did not exhibit any disruption of the Golgi complex or mislocalisation of Golgi markers (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The same isoform has also been found associated with synaptic vesicles (Guo et al, 2003). In addition to the Golgi complex, PtdIns4KII␣ and PtdIns4KII␤ both localise to endosomal membranes containing internalised transferrin and angiotensin (Balla et al, 2002) and EEA1 (Balla et al, 2002;Waugh et al, 2003a).…”
Section: Introductionmentioning
confidence: 82%
“…Adenosine targets both PI4KII types α and β isoforms, whereas wortmannin inhibits PI4KIII types α and β. Inhibition of either PI4KII or PI4KIII enzymes reduces KCNQ2/3 currents (40% with adenosine, 15% with wortmannin). PI4KIIα, originally cloned from chromaffin granules (24), traffics throughout secretory pathways and has been suggested to be present in the trans-Golgi network, endosomes, and transport vesicles (26,(65)(66)(67); PI4KIIβ is found in the cytosol, trafficking vesicles, and clathrin-coated vesicles (68)(69)(70). Taking into account the apparent localization of PI4KII isoforms along different stages of the secretory pathway, it is logical that addition of adenosine has similar effects on PM PI(4,5)P 2 as depletion of the trans-Golgi PI(4)P pool (compare Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Type IIα and IIβ PI4Ks are membrane-bound proteins due to the palmitoylation of a conserved stretch of cysteines in their catalytic domains (24). Immunocytochemical analysis has revealed that they are mostly associated with trans-Golgi, endoplasmic reticulum, and endosomal membranes (25)(26)(27). These type IIα and IIβ enzymes are blocked by adenosine and calcium, but are resistant to wortmannin.…”
mentioning
confidence: 99%
“…It has been reported that PI4KIIa is important for Wnt signaling in Xenopus embryos and interacts with Dvl (Pan et al, 2008;Qin et al, 2009). Waugh et al (2003) reported that PI4KIIa colocalized with valosincontaining protein, a potential prognostic marker for cancer. Xu et al (2006) found that PI4KIIa is associated with cellugyrin-positive Glut4 vesicles.…”
Section: Introductionmentioning
confidence: 99%